A danger to self and others: Health and criminal consequences of involuntary hospitalization - Natalia Emanuel; Pim Welle; Valentin Bolotnyy (Federal Reserve Bank of New York, 2025)
Involuntary hospitalization of people experiencing a mental health crisis is a widespread practice, 2.4 times as common as death from cancer and as common in the U.S. as incarceration in state and federal prisons. The intent of involuntary hospitalization is to prevent individuals from harming themselves or others through incapacitation, stabilization, and medical treatment over a short period of time. Does involuntary hospitalization achieve its goals? We leverage quasi-random assignment of the evaluating physician and administrative data from Allegheny County, Pennsylvania, to estimate the causal effects of involuntary hospitalization on harm to self (proxied by death by suicide or overdose) and harm to others (proxied by violent crime charges). For individuals whose cases are judgment calls, where some physicians would hospitalize but others would not, we find that hospitalization nearly doubles both the probability of dying by suicide or overdose and also nearly doubles the probability of being charged with a violent crime in the three months after evaluation. We provide evidence of earnings and housing disruptions as potential mechanisms. Our results suggest that, on the margin, the system we study is not achieving the intended effects of the policy.
Keywords: I18; I12; K14; 330; involuntary commitment; psychiatric detention; mental health treatment